INDUÇÃO DA BROTAÇÃO E ATIVIDADE ENZIMÁTICA DE GEMAS DE MACIEIRA MEDIANTE APLICAÇÃO DE ÓLEOS VEGETAIS E MINERAL - Marchi, Thiago (2015)
The bud breaking of temperate fruit trees in low wintry chill accumulation regions is mainly carried out with hydrogen cyanamide, a compound that has a high acute toxicity and being restricted markets. Therefore new alternatives need to be studied. Field experiments were designed to verify the efficiency of vegetable oils mixed with mineral oil in the bud breaking and changing the activity of catalase and peroxidase enzymes in apple tree buds. The following products were used for the treatment mix: hydrogen cyanamide (Dormex®, 520 g L?¹ a.i.), mineral oil (Assist®, 756 g L?¹ a.i.), emulsifiable vegetable oil (Natur`óleo®, 930 g L?¹ a.i.) and also vegetable oils of soybean, corn, sunflower and reuse. Since no emulsifier was used emulsifiable vegetable oils detergent. The different treatments were tested under controlled conditions, using the methodology of biological testing detached branches; in adult plants of 13 years old; and plants in training and start of production two years. The application of the mixture of hydrogenated cyanamide and mineral oil resulted in a high percentage of bud break, reduced the catalase enzyme activity and reduced plant vigor, but this treatment reduces fruit set, a factor that may result in lower production. The vegetable oil, mixed with mineral oil, can be a good alternative to induce sprouting, however there is a positive response to the increase in concentration which should be further investigated. The different vegetable oil sources did not appear to influence differently the percentage of shooting. The induction of budding by the application of vegetable and mineral oil did not alter the activity of the enzyme catalase 24 hours after application. Hydrogen cyanamide, mineral oil and vegetable oils did not affect the peroxidase activity 24 hours after application. The bud breaking with vegetable and mineral oil has the potential to produce similar as to mixture of hydrogen cyanamide and mineral oil. New studies of dosage readjustment should consider reducing fruit set and productivity, as well as the percentage of shooting.